2010
DOI: 10.1073/pnas.1010732107
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community transcriptomes reveal microbes and metabolic pathways associated with dissolved organic matter turnover in the sea

Abstract: Marine dissolved organic matter (DOM) contains as much carbon as the Earth's atmosphere, and represents a critical component of the global carbon cycle. To better define microbial processes and activities associated with marine DOM cycling, we analyzed genomic and transcriptional responses of microbial communities to high-molecularweight DOM (HMWDOM) addition. The cell density in the unamended control remained constant, with very few transcript categories exhibiting significant differences over time. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
353
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(391 citation statements)
references
References 52 publications
31
353
1
2
Order By: Relevance
“…TonB-dependent transporters from a variety of taxonomic groups were the most abundant family of membrane proteins identified in a metaproteomic analysis of samples from the South Atlantic (Morris et al, 2010). TonB-related proteins were also identified as among the most abundant transcripts assigned to Idiomarinaceae and Alteromonadacea in a marine microcosm enriched with high molecular weight dissolved organic matter (McCarren et al, 2010). As mentioned above, ABC transporters from Flavobacterales were not found to be abundant in a coastal metatranscriptome .…”
Section: Nutrient Acquisition Strategies Of Monterey Bay Rhodobacteramentioning
confidence: 94%
“…TonB-dependent transporters from a variety of taxonomic groups were the most abundant family of membrane proteins identified in a metaproteomic analysis of samples from the South Atlantic (Morris et al, 2010). TonB-related proteins were also identified as among the most abundant transcripts assigned to Idiomarinaceae and Alteromonadacea in a marine microcosm enriched with high molecular weight dissolved organic matter (McCarren et al, 2010). As mentioned above, ABC transporters from Flavobacterales were not found to be abundant in a coastal metatranscriptome .…”
Section: Nutrient Acquisition Strategies Of Monterey Bay Rhodobacteramentioning
confidence: 94%
“…Alteromonas are typically not very common in the oceans (Eilers et al, 2000) yet are often identified in rRNA-based analyses of microbial communities in open water, and thus naturally co-occur with Prochlorococcus (García- Martínez et al, 2002;Ivars-Martinez et al, 2008;Lopez-Perez et al, 2012). They are metabolically-versatile copiotrophs (Pedler et al, 2014), rapidly responding to increases in dissolved organic matter and often dominating mesocosm experiments (McCarren et al, 2010). Several Alteromonas strains have been shown to inhibit eukaryotic phytoplankton such as diatoms, dinoflagellates and raphidophytes (reviewed by Mayali and Azam, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bacterial mRNA pools have provided assays of the bioreactive components of dissolved organic carbon pools based on transcriptome changes in amended seawater (McCarren et al, 2010;Poretsky et al, 2010;Shi et al, 2012); identified bacterial degradation pathways based on shifts in mRNA composition with increased substrate concentrations (Vila-Costa et al, 2010); characterized short-term reactions to altered CO 2 (Gilbert et al, 2008) and pollutant concentrations (de Menezes et al, 2012); and revealed niche differentiation among co-occurring autotrophs (Liu et al, 2012) and heterotrophs (Gifford et al, 2012). Changes in transcript inventories provide a sensitive window into the fluctuating cues perceived by microbes in their environment, and therefore the signals that drive changes in ecosystem function.…”
Section: Response Of Mrna Levels To Environmental Cuesmentioning
confidence: 99%